An Early Development Process of an Augmented Reality-Based Healthy Diet Tool Prototype - Nur'Aina Norhalim; Azniah Ismail (International Journal of Multimedia and Recent Innovation, 2020)
This paper presents an early development process of an augmented reality-based healthy diet tool prototype i.e. getting the initial requirements for the prototype. This tool is being developed using the evolutionary prototype model. Thus, the tool development will follow several complete 4-phase iterations of the prototype model. To get the initial requirements, we have analysed several existing applications that are related to diet, food and cooking. We found out that the augmented reality is not a common feature. We had also conducted an interview with one of 2018 diet challenge participants. The interviewee welcomed the idea of having augmented reality in the diet tool with a condition that the feature should be designed to accommodate the users. Therefore, several iterations will be conducted to get the best specifications for a diet tool prototype and finding the best ways to embed the augmented reality features into the tool. We will also validate with experts sets of menu, advice and instructions to be used in the tool. It is hoped that our effort will help in developing a reliable, healthy diet tool with suitable augmented reality feature.